Community-Driven Development in Post-Conflict and Conflict-Affected Areas : Experiences from East Asia - Barron, Patrick (World Bank, Washington, DC, 2017)
Community-Driven Development (or CDD) projects are now a major component of World Bank assistance to many developing countries. While varying greatly in size and form, such projects aim to ensure that communities have substantive control in deciding how project funds should be used. The proponents of CDD believe that giving beneficiaries the power to manage project resources will lead to more efficient and effective use of financial resources. It is also claimed that project-initiated participatory processes can have wider 'spillover' impacts, building local institutions and leadership, enhancing civic capacity, improving social relations and boosting state legitimacy. This paper briefly reviews the World Bank's experience of using CDD in conflict-affected and post-conflict areas of the East Asia and Pacific region. This paper provides a framework for assessing the impacts of CDD projects in post-conflict and conflict-affected areas. It tries to unpack the potential causal channels through which projects may have their desired, or other, impacts. The paper concludes with a short summary of what we know, what we don't, and potential future directions for research and programming.